How much do Nepalese mothers know about child development?. Issue 1 (2nd January 2019) - Shrestha, Merina; Ulak, Manjeswori; Strand, Tor A.; Kvestad, Ingrid; Hysing, Mari
ABSTRACT: Parental knowledge on child development is important for maximal developmental potential. This study was conducted to assess mothers' knowledge on child development in Nepal. The Caregivers Knowledge of Child Development Inventory (CKCDI) was used to interview mothers. Total of 1272 mothers were interviewed. Out of the total CKCDI score of 40, mean score (SD) obtained by mothers was 20 (4.8). Mothers' knowledge on the developmental milestone composite was better than stimulation composite with scores of 11.14 (3.09) and 8.9 (3.17), respectively ( p  < .005). Few mothers (38%) identified the correct ages of developmental milestones. Although most of the mothers knew about teaching their children to count or name colors, few knew when to start to read with children. With low level of knowledge on child development among Nepalese mothers, early childhood development programmes should be considered integrated with other health care programmes targeting young children and families.